Socializing the classroom social networks and online learning - Barnes, Susan B. (Lexington Books, 2012)
"Socializing the Classroom: Social Networks and Online Learning, by Susan B. Barnes, examines how social media can be used in education through two research grants and real-world applications. Barnes analyzes social media including Facebook, Courseware, and Second Life, while providing a theoretical foundation for examining social software. A new generation of students is surrounded by digital technologies, leading scholars and teachers to consider virtual worlds to engage students"-- Provided by publisher.